THE MOMENTS FOR NEW (p, q)-ANALOGUE OF BALAZS-SZABADOS OPERATORS - Hamal, Hayatem; Sabancigil, Pembe (Baku State Univ, Inst Applied Mathematics, 2020)
[Abstract Not Available]
7th International Conference on Control and Optimization with Industrial Applications (COIA) -- AUG 26-28, 2020 -- ELECTR NETWORK
Keywords: (p, q)-integers; Moments; Balazs-Szabados Operators; (p, q)-Balazs-Szabados Operators